Modern philosophical and legal discussions about justice - Podkovenko, Tetiana; Racyn, Volodymyr (Actual problems of law (Aktual’ni problemi pravoznavstva), 2023)
The article is aimed at researching the peculiarities of modern approaches to the understanding of justice. The authors note that the topic of justice is one of the updated ideas in philosophical and legal research and is considered quite widely - both in the traditional moral, legal, and economic, socio-political sense. The idea of justice permeates all spheres of social life and reflects rather complex dialectical processes of the legal development of society at various historical stages. Studying the problems of justice provides an opportunity to gain a deeper understanding of the meaning and content of modern state- and law-making processes. Justice is a fundamental principle of law and is an integral multifaceted phenomenon. The authors emphasize the special relationship between law and justice. Law is based on the idea of justice and is normatively established justice. Only in this aspect it is possible to talk about the legal law as a real and effective means of ensuring the rights and interests of a person. The authors note that justice is also a universally recognized value of modern civil society, as it is enshrined in the documents of the world community, including the Universal Declaration of Human Rights, the UN International Covenants, the Convention for the Protection of Human Rights and Fundamental Freedoms. Accordingly, the rethinking of justice, the emergence of new concepts are closely related to the changes taking place in the political, economic and legal spheres of a certain society. As the research shows, such a concept as justice is quite ambiguous. Especially when it comes to justice in law. It has its own specific features, but it is still the basis of law. So, it becomes clear that this is an ideal that is very difficult to achieve. At the same time, justice is considered a rather subjective category and cannot be the same for everyone. So, the law makes attempts to get closer to a certain "imperfect ideal", but the need for justice is the motive through which humanity created the law. Thus, it can be concluded that justice and law are those categories that are inextricably linked, and they are integral parts of each other. It is their reality, their practical need for society that confirms their viability.